DataSheet1_Controlling influence of water and ice on eruptive style and edifice construction in the Mount Melbourne Volcanic Field (northern Victoria Land, Antarctica).pdf - J. L. Smellie; S. Rocchi; G. Di Vincenzo (2023)
The Mount Melbourne Volcanic Field (MMVF) is part of the West Antarctic Rift System, one of Earth’s largest intra-continental rift zones. It contains numerous small, compositionally diverse (alkali basalt–benmoreite) flank and satellite vents of Late Miocene–Pliocene age (≤12.50 Ma; mainly less than 2.5 Ma). They demonstrate a wide range of morphologies and eruptive mechanisms despite overlapping compositions and elevations, and they occur in a relatively small area surrounding the active Mount Melbourne stratovolcano. The volcanic outcrops fall into several main categories based on eruptive style: scoria cones, tuff cones, megapillow complexes, and shield volcanoes. Using the analysis of lithofacies and appraisal of the internal architectures of the outcrops, we have interpreted the likely eruptive setting for each center and examined the links between the environmental conditions and the resulting volcanic edifice types. Previous investigations assumed a glacial setting for most of the centers but without giving supporting evidence. We demonstrate that the local contemporary environmental conditions exerted a dominant control on the resulting volcanic edifices (i.e., the presence or absence of water, including ice or snow). The scoria cones erupted under dry subaerial conditions. Products of highly explosive hydrovolcanic eruptions are represented by tuff cones. The water involved was mainly glacial (meltwater) but may have been marine in a few examples, based on a comparison of the contrasting internal architectures of tuff cones erupted in confined (glacial) and unconfined (marine, lacustrine) settings. One of the glaciovolcanic tuff cones ceased activity shortly after it began transitioning to a tuya. The megapillow complexes are highly distinctive and have not been previously recognized in glaciovolcanic successions. They are subglacial effusive sequences emplaced as interconnected megapillows, lobes, and thick simple sheet lavas. They are believed to have erupted at moderately high discharge and reduced ...